BIOMECHANICAL FEATURES OF SINGLE-BONE OSTEOSYNTHESIS OF DIAPHYSEAL FRACTURES IN CHILDREN BY THE TITANIUM ELASTIC NAILS - Levytskyi, A.F.; Terpylovskyi, Yu.R.; Yaresko, O.V. (World of Medicine and Biology, 2022)
The purpose of the study was to investigate the changes in stress-strain in the forearm bones in diaphyseal fracture of both bones when fixing a fracture of only one bone with titanium elastic nails compared to normal and to determine the type of fixation that best provides conditions for optimal fracture consolidation. We used the finite elements method for numerical analysis of the stress-strain state in the forearm bones. The model was based on tomographic sections of bone. A transverse fracture in the middle of the diaphysis of the ulna and radius was modeled and variants of the model with osteosynthesis with titanium elastic fracture nails of either the ulna only or the radial bone were constructed. The developed biomechanical model “Diaphysis of the forearm bones – metal fixator” demonstrates a moderate increase in internal stress at the fracture site using titanium elastic nails , which can help create optimal conditions for reparative osteogenesis; the greatest changes in the stress-strain state in both types of osteosynthesis in comparison with the norm occurred in the simulation of torsion, especially in the ulna. A significant increase in the stress-strain state in the fracture area of the ulna with its isolated osteosynthesis can lead to complications in the form of delayed union or the formation of a nonunion (even a break of the fixator with the wrong selection of its diameter). Thus, in the case of a fracture of both bones of the forearm, even with a stable fracture of the radial bone, it is not recommended to fix only the ulna. It is better to fix both bones according to standard methods. In addition, in the case of both forearm bones’ fracturing with a stable fracture of the ulna, you can limit osteosynthesis of the radial bone only.
Keywords: children; fracture of forearm bones; biomechanics; osteosynthesis; stress-strain state